Community perception of climate events as a security issue: The case of Hatiya Island, Bangladesh - Suza, Ma; Warner, Jeroen; Pacillo, Grazia; Läderach, Peter; van Dijk, Han (Liverpool University Press, 2024)
This study delves into the multifaceted dynamics linking climate change and conflict on Hatiya Island, Bangladesh. Examining perceptions and responses to climate-induced stress, insecurity and potential conflicts, our research draws insights from literature reviews and focus group discussions. Despite the heightened stress resulting from unpredictable climate events, islanders perceive recent improvements in food security. They continue to struggle with periodic shortages and inaccessible health care and education. Many are entrapped in a cycle of poverty, debt and political marginalisation, further compounded by exploitative economic relations, power dynamics and government policies that intensify grievances. Climate change impacts are not perceived locally as an (immediate) threat: other issues seem to have more priority. Our findings emphasise the importance of prioritising social and political dynamics, alongside structural constraints, in understanding the climate–conflict nexus. This should not be taken to mean that climate change is irrelevant, though, as it has an impact on the bedrock of long-term poverty and distress.